Fresno County Economic Opportunities Commission 20 Year Anniversary Dinner; Julian Bond Keynote Speaker - Watkins, Howard::::::::: (1985)
Paulette Riddlesprigger, Jr., Bill Riddlesprigger, Jr., Wilma Francis and Charles Francis